An optimized lead-free formamidinium Sn-based perovskite solar cell design for high power conversion efficiency by SCAPS simulation - Kumar, Manish; Raj, Abhishek; Kumar, Arvind; Anshul, Avneesh (Optical materials, 2020)
An organic-inorganic perovskite formamidinium tin iodide (HC(NH2)2SnI3– FASnI3) is used as light absorbing layer in photovoltaics due to its lead-free nature, wider bandgap of 1.41 eV and better temperature stability than CH3NH3SnI3. In the present investigations, SCAPS simulation with comparison to the experimental as well as simulation data for FASnI3-based solar cell device is accomplished for high power conversion efficiency with proper optimization. The variation in the device design key parameters such as absorber, hole transport layer and electron transport layer thickness including defect density, doping concentration in absorber, carriers capture cross sections and interfacial defects are examined with their impact on device performance. The preliminary structure of device is based on the reported experimental and simulation work with the efficiency of 1.75% and 1.66%, respectively. After the SCAPS simulation with the optimization of basic parameters in this work, the final optimized performance parameters of the solar cell device are found to be enhanced with short-circuit current density (Jsc) of 31.20 mA/cm2, open-circuit voltage (Voc) of 1.81 V, fill factor (%FF) of 33.72% and power conversion efficiency (%PCE) of 19.08%. [Display omitted] •Physics behind the performance parameters in (HC(NH2)2SnI3– FASnI3) PSC device.•Comparison FASnI3-based PSC performance with reported experimental and SCAPS simulation results.•Study the effect on the device with the variation of basic parameters of cell.•Final optimized parameters achieved: Jsc-31.20 mA/cm2, Voc-1.81 V, FF-33.72% and PCE-19.08%.